Evaluation of Antioxidant Activities and Tyrosinase Inhibitory Effects of Ginkgo biloba Tea Extract - Pongsathorn Klomsakul; Arisara Aiumsubtub; Pornchanok Chalopagorn (The Scientific World Journal)
Ginkgo biloba L. (Ginkgoaceae) is one of the best-selling products, popular in nutritional properties and health benefits. In the present study, the total phenolic compounds and flavonoid content of the ethanolic extract from G. biloba tea were also evaluated. Furthermore, the antioxidant activity was determined using DPPH assay and tyrosinase inhibitory activity was also determined with L-DOPA as a substrate. The extract showed the total phenolic compound and flavonoid content were 14.13 mg GE g−1 extract and 71.33 mg rutin equivalence g−1 DW, respectively. Taking into account the results of the DPPH, the antioxidant property at the concentration of 500 µg ml−1 was 95.29% that is similar to that of the BHT, ascorbic acid, and gallic acid used as positive controls. The inhibitory capacity of the sample against tyrosinase is lower than that of positive controls at all concentrations. The results of inhibition in terms of IC50 confirm the inhibition patterns. On the other hand, the statistical similarity of the anti-DOPA auto-oxidation (IC50) of G. biloba leaf extract and kojic acid was found (456.27 and 418.5 µg ml−1) but was lower than that of ascorbic acid (IC50 989.61 µg ml−1). A relationship was observed between the potential of antioxidant activity, tyrosinase inhibition, and anti-DOPA auto-oxidation with concentration levels of the extracts. The results of phytochemical analysis revealed the presence of tannins, flavonoids, terpenoids, and reducing sugars.